The analysis of spatial distributions, origins of caldera-forming eruptions with basaltic-andesitic magma compositions, and genesis of Miocene ignimbrites of the Eastern volcanic belt, Kamchatka - O. V. Bergal-Kuvikas; A. N. Rogozin; E. S. Klyapitsky (Геодинамика и тектонофизика)
Based on the statistical data of the Global Volcanism Program of the Smithsonian Institution and published materials, we present a comparative analysis of caldera-forming eruptions on global scale. The geodynamic settings and genesis of the caldera-forming eruptions with basaltic-andesitic magma compositions are described. The origin of the majority of mafic ignimbrites was related with external water. Such ignimbrites were generated in a submarine environment or with a contact with water. The newly obtained data, paleogeodynamic reconstruction and geological mapping of Miocene mafic ignimbrites of the Eastern volcanic belt (EVB) of Kamchatka confirm their genesis in costal-marine environment. These new data show significance of paleoreconstructions in studies of paleo-volcanoes and relief-forming pyroclastic rocks.